A Review of Different Stimulation Methods for Functional Reconstruction and Comparison of Respiratory Function after Cervical Spinal Cord Injury. (17th September 2020) - Chang, Jiaqi; Shen, Dongkai; Wang, Yixuan; Wang, Na; Liang, Ya
Abstract : Background . Spinal cord injury (SCI) is a common severe trauma in clinic, hundreds of thousands of people suffer from which every year in the world. In terms of injury location, cervical spinal cord injury (CSCI) has the greatest impact. After cervical spinal cord injury, the lack of innervated muscles is not enough to provide ventilation and other activities to complete the respiratory function. In addition to the decline of respiratory capacity, respiratory complications also have a serious impact on the life of patients. The most commonly used assisted breathing and cough equipment is the ventilator, but in recent years, the functional electrical stimulation method is being used gradually and widely. Methods . About hundred related academic papers are cited for data analysis. They all have the following characteristics: (1) basic conditions of patients were reported, (2) patients had received nerve or muscle stimulation and the basic parameters, and (3) the results were evaluated based on some indicators. Results . The papers mentioned above are classified as four kinds of stimulation methods: muscle electric/magnetic stimulation, spinal dural electric stimulation, intraspinal microstimulation, and infrared light stimulation. This paper describes the stimulation principle and application experiment. Finally, this paper will compare the indexes and effects of typical stimulation methods, as well as the two auxiliary methods: training and operation. Conclusions . Although there is limited evidence for the treatment of respiratory failure by nerve or muscle stimulation after cervical spinal cord injury, the two techniques seem to be safe and effective. At the same time, light stimulation is gradually applied to clinical medicine with its strong advantages and becomes the development trend of nerve stimulation in the future.